2023
DOI: 10.1021/acs.est.2c09090
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Tetrabromobisphenol A and S to Human Serum Albumin Is Weakened by Coexisting Nanoplastics and Environmental Kosmotropes

Abstract: Human serum albumin (HSA) was used as a model protein to explore the effects of brominated flame retardant (BFR) binding and the corona formation on polystyrene nanoplastics (PNs). Under physiological conditions, HSA helped to disperse PNs but promoted the formation of aggregates in the presence of tetrabromobisphenol A (TBBPA, ΔD h = 135 nm) and S (TBBPS, ΔD h = 256 nm) at pH 7. At pH 4, these aggregates became larger with fewer electrostatic repulsion effects (ΔD h = 920 and 691 nm for TBBPA and TBBPS, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The results, listed in Table 1, showed that the K SV values were negatively correlated with temperature. The K q values obtained were higher than 2.0 × 10 10 M −1 s −1 [16], indicating that static quenching was the dominant mechanism of BSA quenching with HES 200/0.5, which was initiated by the formation of a complex [17].…”
Section: Resultsmentioning
confidence: 99%
“…The results, listed in Table 1, showed that the K SV values were negatively correlated with temperature. The K q values obtained were higher than 2.0 × 10 10 M −1 s −1 [16], indicating that static quenching was the dominant mechanism of BSA quenching with HES 200/0.5, which was initiated by the formation of a complex [17].…”
Section: Resultsmentioning
confidence: 99%